Expulsive choroidal haemorrhage - Srinivasan M (Indian Journal of Ophthalmology, 1992)
Expulsive choroidal haemorrhage is a dramatic and serious complication of cataract surgery that occurred in five patients out of ten thousand consecutive cataract surgeries performed by the author during the year 1989 and 1990. Report about this dreaded complication after cataract surgery are scanty and as far as I can remember I have not seen any report in Indian ophthalmic literature recently. Since cataract surgery forms the major part of intra ocular surgeries performed in our country, I thought it would be appropriate to report about this rare complication which may occur to all of us. Out of five cases 3 were males and 2 were females in the age group ranging between 45-72 years. Two eyes regained vision up to 6/12 after intra operative expulsive haemorrhage. All the eyes were salvaged by doing anterior sclerotomy. Diabetes, hypertension, glaucoma and myopia are the commonest predisposing factors.